The impact of end-to-end encryption on the security of digital banking transactions: an in-depth analysis - Irsyad, Ziqrurrahman; Indraningsih, Nurul Hidayati (Institute of Computer Science (IOCS), 2024)
This study aims to evaluate the impact of end-to-end encryption (E2EE) on the security of digital banking transactions through a systematic literature review method. The literature sources are from Scholar, DOAJ, and Scopus indexers in the last ten years. The analysis confirmed that E2EE plays a crucial role in enhancing the security of digital banking transactions. Data inclusion criteria included empirical studies, literature reviews, and other research articles that directly addressed the implementation, benefits, or challenges of E2EE in digital banking transactions. The research procedure began with the formulation of research questions, development of a research protocol, systematic literature search, screening of search results, and data extraction and analysis to identify key findings, trends, and research gaps. E2EE has proven to be effective in maintaining confidentiality, data integrity, and protecting information from unauthorized access and eavesdropping. The implementation of E2EE, especially in cloud storage and mobile banking, strengthens security measures and reduces the risk of fraudulent activities. The findings underscore the importance of E2EE adoption to strengthen security systems in the digital banking sector. The study further recommends further research into the integration of E2EE with blockchain technology and its implications for information security policies.